(untitled) (Al-Qamar, 2022)
Ibn e Arabi is a renowned Sufi Philosopher of twelfth century, in Islamic Tradition. Beside his other books, Tafsīr Ibn e Arabi is a prominent exegesis of Qur’an of Ishari (Sufi) Tradition. His Tafsīr carries the convention of explaining Qur’anic themes, in the light of his claimed mystic revelation, though he has aligned his interpretations, at some of the occasions, with traditional Mathūr Tafsīr. The following article explores the specific interpretation of Ilm al-Wahy (Divine Wisdom through revelation), given by Ibn e Arabi in his Tafsīr., vis a vis traditional Mathūr Tafsīr.